Energy and entropy analyses of hydrate dissociation in different scales of hydrate simulator - Feng, Jing-Chun; Wang, Yi; Li, Xiao-Sen (Energy, 2016)
To investigate the effect of the reservoir scale on hydrate dissociation by depressurization in conjunction with warm water stimulation with dual horizontal wells, experiments of hydrate dissociation by such method have been carried out in CHS (Cubic Hydrate Simulator) and PHS (Pilot-scale Hydrate Simulator). The results show that there is little difference of temperature variation during the depressurizing stage with different scales of hydrate simulator. However, during the constant-pressure stage (the injection stage), the difference is obvious, and the heat transfer rate in the PHS is faster than that in the CHS. Additionally, the system entropy production during the injection stage is the largest, implying that the injection stage is the main source of energy consumption. Moreover, both the ratio of the amount of the dissociated gas in the PHS to that in the CHS and the ratio of the entropy production for hydrate dissociation with the PHS to that with the CHS approximately equal to the volume ratio of the PHS to the CHS. (C) 2016 Elsevier Ltd. All rights reserved.